2009
DOI: 10.1017/s1355617709991123
|View full text |Cite
|
Sign up to set email alerts
|

Long-term skill proceduralization in schizophrenia

Abstract: Previous studies had revealed no specific effect under haloperidol (typical) and risperidone (atypical) neuroleptic (NLP) treatments for schizophrenia (SZ) on a variety of neurocognitive functions relying on the dopaminergic meso-cortico-limbic system (Rémillard et al., 2005, 2008). Considering the different affinities of D2 dopamine receptors for typical and atypical NLPs, these drugs may differentially affect the functions of the striatum, a determinant brain structure involved in procedural learning. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In a prospective study, Harris et al (2009) found that first-episode drug-naïve patients subsequently treated with risperidone became impaired on a predictive saccade task. Recently, Rémillard et al (2010) reported that risperidone does not impair the same procedural learning tasks as typical antipsychotics. Patients randomly assigned to either haloperidol or risperidone performed a task involving semantically related inverted word pairs, with the haloperidol group having greater impairment than the risperidone group at all assessment periods showing that the two drugs are not identical in their effects on this task.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Harris et al (2009) found that first-episode drug-naïve patients subsequently treated with risperidone became impaired on a predictive saccade task. Recently, Rémillard et al (2010) reported that risperidone does not impair the same procedural learning tasks as typical antipsychotics. Patients randomly assigned to either haloperidol or risperidone performed a task involving semantically related inverted word pairs, with the haloperidol group having greater impairment than the risperidone group at all assessment periods showing that the two drugs are not identical in their effects on this task.…”
Section: Discussionmentioning
confidence: 99%
“…Other tests applied to assess procedural learning in schizophrenia include the Tower of Toronto (Bedard et al, 2000; Purdon et al, 2003), Tower of Hanoï (Goldberg et al, 1990), mirror drawing tasks (Bedard et al, 1996a; Bedard et al, 2000; Paquet et al, 2004; Scherer et al, 2004), serial reaction time tasks (Harris et al, 2009; Kern et al, 1998; Siegert et al, 2008), periodic sequence learning tasks (Kumari et al, 2002), rotary pursuit (Kern et al, 1998; B.L. Schwartz et al, 1996), computed visual tracking tasks (Paquet et al, 2004) and non-motor (verbal) procedural learning tests (Remillard et al, 2010). The results from these studies suggest that patients with schizophrenia demonstrate procedural learning, but that their learning profile may be impaired compared to healthy controls, potentially due to medication (Bedard et al, 2000; Kumari et al, 2002; Purdon et al, 2003; Purdon et al, 2002; Remillard et al, 2010; Stip, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz et al, 1996), computed visual tracking tasks (Paquet et al, 2004) and non-motor (verbal) procedural learning tests (Remillard et al, 2010). The results from these studies suggest that patients with schizophrenia demonstrate procedural learning, but that their learning profile may be impaired compared to healthy controls, potentially due to medication (Bedard et al, 2000; Kumari et al, 2002; Purdon et al, 2003; Purdon et al, 2002; Remillard et al, 2010; Stip, 2006). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation